INTERPRETATION OF EASTERN PHILOSOPHY AND ISLAM IN PUSHKIN'S CREATION - Ishonkhanova Iroda Abduvakhitovna (American Journals, 2024)
Alexander Sergeevich Pushkin, the sun of Russian literature, showed interest and attention to Eastern philosophy, especially Islam. This article mentions some considerations on this topic.
Keywords: “Bakhchisarai Fountain”, “Eugene Onegin”, “Talisman”, “Prophet”, “Imitations of the Koran”.